Higher Education and the Politics of the Radical Imagination - Giroux, Henry A (PRISM: Casting New Light on Learning, Theory and Practice, 2018)
In this paper, I address the vital civic principle that democracies cannot exist without informed citizens and that education itself must be about more than training and is essential to creating critical and engaged citizens. Such an understanding is imperative at a time when democracy is under siege all over the globe. As an example of both the rise of authoritarianism and the challenge it poses to higher education, I focus on not only the election and presidency of Donald Trump but also an emboldened culture of manufactured illiteracy that exhibits a disdain for any notion of education wedded to the pursuit of the truth, science, and the public good. I argue that the Trump administration is engaged in not simply a neoliberal political project designed to consolidate wealth and power in the hands of the financial elite, but also is reworking of the very meaning of education both as an institution and as a broader cultural force. Democracy and politics itself are both in crisis and under siege. The central issue for this essay is what it might mean for educators to take seriously the notion that democracy should be a way of thinking about education - one that thrives on connecting equity to excellence, learning to ethics, and agency to the imperatives of social responsibility and the public good. Regarding the discourse of civic courage, social responsibility and the ethical imagination, I argue that civic literacy is crucial to a democracy and that the university must play a vital role in creating the formative cultures that make critically engaged citizens possible. In addition to taking up these issues, I will point to several recommendations that provide an alternative to some of the oppressive conditions now shaping institutions of higher learning, particularly in the United States. In doing so, I conclude with a particular emphasis on the need for educators to develop a new language of governance accompanied by reclaiming the discourse of civic courage and the ethical imagination, all of which I believe are central to any viable notion of transformative democratic change.